Yakutsk Region in the Administrative-Territorial Structure of Asian Russia in the XIX Century - A. I. Arkhipova (Научный диалог, 2018)
The projects of management of administrative-territorial entities of Siberia, proposed in the XIX century in which a special place is given to the Yakut region are considered. This problem is relevant in view of the continuing research interest in the issues of imperial regionalism, in connection with which a scientific school has emerged to study this phenomenon. It is noted that scientists identified four stages in the process of entering the territories of Siberia and the Far East into the imperial system. The work uses the problem-chronological, structural-functional, historical-comparative and retrospective methods. The author focuses her attention on the issue of expanding the administrative independence of the region during the administration of the Governor-General N. N. Muravyov-Amursky. It is noted that the diversity of projects was associated both with the personal views of the governor-generals of Eastern and Western Siberia, and with the degree of integration of the territory into the general imperial space. It is shown that the search for the most optimal model of control over the vast territory of Siberia continued throughout the XIX century. The author comes to the conclusion that the north-east of Russia was constantly in the field of view of the governor-generals, and the regional structure established in the 19th century seemed to be the most optimal.